ANALISIS MOTIVASI KERJA DALAM PENINGKATAN KINERJA GURU DI SMK NEGERI 2 PROBOLINGGO - Gatot Subroto (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
The aims of the study are to determine, analyze and assess work motivation, teacher performance, factors that inhibit performance improvement, and strategies to increase work motivation in SMKN 2 Probolinggo. This study used qualitative methods through observation, interviews, and documentation studies with primary data sources, such as the result of interviews and observation. Meanwhile the secondary data sources, such as literature studies from books, records and internet sites used in this study. Data analysis techniques by reducing data, presenting data, making conclusions, and verification. The result showed that the motivation to improve teacher performance can be done by increasing competence, giving incentives or rewards, and improving the work environment.